Pengaruh Motivasi Kerja dan Organizational Citizenship Behavior (OCB) terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening - Lupnaya Mara Aruly; Mawar Ratih Kusumawardani (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of work motivation and organizational citizenship behavior (OCB) on employee performance and examine the role of job satisfaction as a mediating variable at the Kediri Regency Manpower Office. This study employed a quantitative design with a survey method, involving the entire employee population of 32 through a saturated sampling technique. Data were obtained through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, and mediation analysis. The results indicate that work motivation and organizational citizenship behavior (OCB) have a positive and significant effect on job satisfaction, with OCB being the strongest contributing factor. However, work motivation and OCB do not have a direct and significant effect on employee performance. Conversely, job satisfaction has been shown to have a positive and significant effect on performance and can mediate the influence of work motivation and OCB on performance at the Kediri Regency Manpower Office.